Hippocampal cognitive and relational map paradigms explored by multisensory encoding recording with wide-field calcium imaging - Sun, Dechuan; Shaik, Noor E. Karishma; Unnithan, Ranjith Rajasekharan; French, Chris (iScience, 2024)
Two major theories have been proposed to explain hippocampal function: cognitive map and the relational theories. They differ in their views on whether hippocampal neurons can process non-spatial information independently. However, the explanatory power of these theories remains unresolved. Additionally, more complex aspects of hippocampal neural population responses to non-spatial stimuli have not been investigated. Here, we used miniaturized fluorescence microscopy to investigate mouse CA1 responses to spatial, visual, auditory modalities, and combinations. We found that while neuronal populations primarily processed spatial information, they also showed strong sensitivity to non-spatial modalities independent of spatial inputs, exhibiting distinct neuronal dynamics and coding patterns. These results provide strong support for the relational theories. [Display omitted] •The hippocampus can process non-spatial information independently•Hippocampal multisensory encoding supports the relational theory•Non-spatial stimuli induce topological changes in the hippocampal neural network•The hippocampus processes sensory information through various mechanisms Biological sciences; Cognitive neuroscience